Safeguarding Children's Rights in Sport: From Legal Standards to Everyday Practice - Kraljić, Suzana (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
Safeguarding children's rights in sport has become an increasingly important legal issue. While sporting environments offer significant developmental benefits, they may also expose children to risks such as abuse (e.g., sexual, physical, neglect). Today, international legal standards and national legal frameworks impose clear obligations on states and sports organizations to protect children and their rights. This article examines the gap between formal legal requirements in sports and how they are implemented in practice. It also explores the selected international cases and the Slovenian criminal law framework, and relevant Slovenian case-law relevant to the abuse of children in sports.